Application of a metallic-magnetic calorimeter for high-resolution x-ray spectroscopy of Fe at an EBIT - Herdrich, Marc Oliver; Hengstler, Daniel; Allgeier, Steffen; Friedrich, M.; Fleischmann, Andreas; Enss, Christian; Bernitt, S.; Morgenroth, T.; Trotsenko, S.; Schuch, R.; Stöhlker, Th (Journal of physics. B, Atomic, molecular and optical physics, 2024)
In this work, we present an experiment conducted at the S-EBIT-I ion trap of GSI. It involved the study of ion-electron collisions of Fe and Ba ions in various charge states with the electron beam. Characteristic x-ray radiation emitted during the continuous interaction was recorded utilizing an energy-dispersive maXs-30 detector based on metallic-magnetic calorimeter (MMC) technology. Optimizations to the applied sensitivity-drift correction and energy calibration procedures significantly improved the achieved energy resolution compared to previous applications of a similar detector. This made it possible to individually resolve and identify overlapping x-ray lines of iron and barium in a wide spectral range. As a demonstration of the outstanding detector performance, we used the recorded spectral data to extract an estimate of the charge state distribution of Fe ions in the trap. This experiment campaign marks an important milestone in the ongoing effort to enable the deployment of MMC detectors for future high-precision measurements in fundamental physics experiments.